2013
DOI: 10.1051/0004-6361/201220425
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental parameters of bright Ap stars from wide-range energy distributions and advanced atmospheric models

Abstract: Aims. As a well-established procedure for the vast majority of normal main-sequence stars, determination of atmospheric and stellar parameters turns to be a challenging process in case of magnetic chemically peculiar stars. Inhomogeneous distribution of chemical elements and strong magnetic fields make most of the standard photometric and spectroscopic calibrations inapplicable for this class of stars. In this work we make use of available observed energy distributions calibrated to absolute units, stellar par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 44 publications
0
22
1
Order By: Relevance
“…Accepting the global parameters derived by Shulyak et al (2009Shulyak et al ( , 2013, we find that HD 24712 is slightly beyond the red edge of the instability strip derived by Cunha (2002), meaning that in default polar models of this star no high frequencies are expected to be found unstable. If we ignore this fact for a moment and consider the scaling with radius of the envelop of growth rates (ignoring the small mass dependence expected in that scaling), we find, in addition, that the envelope would be centered around 2.0 mHz, for the radius considered, thus significantly out of place in relation to the observed frequencies.…”
Section: Figurementioning
confidence: 57%
“…Accepting the global parameters derived by Shulyak et al (2009Shulyak et al ( , 2013, we find that HD 24712 is slightly beyond the red edge of the instability strip derived by Cunha (2002), meaning that in default polar models of this star no high frequencies are expected to be found unstable. If we ignore this fact for a moment and consider the scaling with radius of the envelop of growth rates (ignoring the small mass dependence expected in that scaling), we find, in addition, that the envelope would be centered around 2.0 mHz, for the radius considered, thus significantly out of place in relation to the observed frequencies.…”
Section: Figurementioning
confidence: 57%
“…We present a compilation of 33 Lib's properties in Table 1. The parameters shown in this table are mostly found in the work of Shulyak et al (2013) where a detailed study of several bright Ap stars was conducted. We note that Kochukhov & Bagnulo (2006) also presented parameters of many chemically peculiar stars, but derive their results through a homogeneous study, rather than from a star-by-star study which is preferable.…”
Section: Librae (Hd 137949)mentioning
confidence: 99%
“…They found that, as with other roAp stars, the pulsation radial velocity (RV) amplitude varied with spectral region and line strength. Furthermore, Shulyak et al (2013) results using the Gaia DR2 parallax. Mkrtichian et al (2003) found at least one radial node in the upper atmosphere of 33 Lib; a conclusion drawn from the anti-phase relation between pulsations measured predominantly in Nd and Nd .…”
Section: Librae (Hd 137949)mentioning
confidence: 99%
See 1 more Smart Citation
“…Surface magnetic field moduli of some roAp stars are plotted with respect to the dominant oscillation frequencies. The magnetic field strengths were taken from Shulyak et al (2013), Ryabchikova et al (2008), Mathys et al (1997), Hubrig et al (2005), Kochukhov et al (2004), Balona et al (2013).…”
Section: Hideyuki Saiomentioning
confidence: 99%